Application of a New Silica Gel Ionization Intensifier on Nanogram Lead Isotope Analysis - LIU Xue-mei; TANG Lei; FU Zhong-hua; LONG Kai-ming (Yankuang ceshi, 2014)
In nuclear forensics the amount of Pb to be analyzed is usually in the order of several nanograms; that is >10-3 of ionization efficiency is required for mass spectrometry measurements. The traditional silica-gel-phosphoric acid loading technique is typically used to measure microgram amounts of Pb, and the ionization efficiency is in the order of 10-4-10-3. Although the boron-silica gel technique could increase the ionization efficiency to 10-3 or higher, it is also difficult to handle measurement conditions as the ion flow repeatedly increased and decay process in the ionization of Pb resulting in the ion emission instability. A new silica gel-perrhenic acid loading reagent method has been developed and exhibits a significant enhancement in the ionization efficiency of Pb. Compared with the boron-silica gel technique, the emission of Pb ions is very stable with this new technique. The measurement Relative Standard Deviation of 204Pb/206Pb, 207Pb/206Pb, 208Pb/206Pb was 0.4%, 0.2% and 0.1%, respectively from 1 ng of pb, which is an improvement over the precision with other silica gel techniques. The enhancement effect on the ion emission of Pb was compared with the silica gel-perrhenic acid and some other traditional silica gel techniques. The reagent amount of the silica gel was optimized to 0.5-3.0 μL and the ‘sandwich biscuit’ loading sequence was used. The ionization efficiency of the Pb reached 6.0×10-3-4.6×10-2 for 1100 ng Pb. The ionization efficiency was close to the boron-silica gel technique, whereas it was about ten times higher than the traditional silica gel-phosphoric acid technique. A stable ion current was obtained by use of the silica gel-perrhenic acid technique, and the measurement accuracy meets the requirements for region indicators on nuclear forensic analysis.